2016
DOI: 10.1093/mmy/myw118
|View full text |Cite
|
Sign up to set email alerts
|

Successful treatment ofAspergillusventriculitis through voriconazole adaptive pharmacotherapy, immunomodulation, and therapeutic monitoring of cerebrospinal fluid (1→3)-β-D-glucan

Abstract: Aspergillus ventriculitis is an uncommon but often fatal form of invasive aspergillosis of the central nervous system (CNS). As little is known about the diagnosis, treatment, and outcome of this potentially lethal infection, we report the strategies used to successfully treat Aspergillus ventriculitis complicating a pineal and pituitary germinoma with emphasis on the critical role of adaptive pharmacotherapy of voriconazole and serial monitoring of (1→3)-β-D-glucan in cerebrospinal fluid. We describe several … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 27 publications
0
16
0
2
Order By: Relevance
“…Recapitulating the findings for the parameters of organism-mediated injury, survival, pulmonary fungal burden, and serial (1¡3)-␤-D-glucan levels, animals treated with ISA60 or ISA60-MFG2 also demonstrated resolution of the elevated GMI in serum. The validity of GMI in reflecting the therapeutic response is buttressed by previous studies with animal models of pulmonary aspergillosis (8,9,13,14) and patients with invasive aspergillosis (15)(16)(17)(18)(19)(20)(21).…”
Section: Figmentioning
confidence: 99%
“…Recapitulating the findings for the parameters of organism-mediated injury, survival, pulmonary fungal burden, and serial (1¡3)-␤-D-glucan levels, animals treated with ISA60 or ISA60-MFG2 also demonstrated resolution of the elevated GMI in serum. The validity of GMI in reflecting the therapeutic response is buttressed by previous studies with animal models of pulmonary aspergillosis (8,9,13,14) and patients with invasive aspergillosis (15)(16)(17)(18)(19)(20)(21).…”
Section: Figmentioning
confidence: 99%
“…TDM‐guided long‐term voriconazole therapy was proved effective in the treatment of central nervous system (CNS) aspergillosis without occurrence of severe adverse events in two young patients who experienced postneurosurgical‐related infections (brain abscess aspergillosis and ventriculitis ).…”
Section: Discussionmentioning
confidence: 99%
“…On an individual patient level, GM-CSF has shown promising results. Chen et al (2017) reported success where GM-CSF was used as adjunct therapy to treat Aspergillus ventriculitis. GM-CSF was given in conjunction with voriconazole, amphotericin B, and caspofungin.…”
Section: Cytokine Therapymentioning
confidence: 99%